2020
DOI: 10.3390/jcm9051555
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 as a Biomarker Candidate of Rheumatoid Arthritis Development

Abstract: There is a need for definite diagnosis of rheumatoid arthritis (RA) at its earliest stages of development in order to introduce early and effective treatment. Here we assessed whether serum interleukin-15 (IL-15) can serve as a new biomarker of RA development in patients with undifferentiated arthritis (UA). Interleukin-15, IgM-rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP Abs) were measured in UA patients at inclusion. Six months later, the diagnosis was re-evaluated, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…The level of IL-15 is increased in the serum and synovial fluid in the early stage of RA, and promotes the release of TNF-a and IL-17 to participate in T lymphatic activation and subsequent bone destruction. It can be used as an independent biomarker for the detection of early RA (169)(170)(171)(172). IL-27 secreted by macrophages has dual antiinflammatory and pro-inflammatory functions.…”
Section: Interaction Of Cell Subsets and Cytokines In Rheumatoid Arthritismentioning
confidence: 99%
“…The level of IL-15 is increased in the serum and synovial fluid in the early stage of RA, and promotes the release of TNF-a and IL-17 to participate in T lymphatic activation and subsequent bone destruction. It can be used as an independent biomarker for the detection of early RA (169)(170)(171)(172). IL-27 secreted by macrophages has dual antiinflammatory and pro-inflammatory functions.…”
Section: Interaction Of Cell Subsets and Cytokines In Rheumatoid Arthritismentioning
confidence: 99%
“…Nonetheless, its levels are elevated during disease [ 114 ] and strongly correlate with rheumatoid factor and ACPA levels [ 115 , 116 ]. Additionally, this interleukin is suspected of taking part in osteoclastogenesis [ 117 ], T cells activation and trafficking [ 115 , 116 ] and stimulating cytokines production. Studies have shown that blockade of IL-15 signal transduction leads to the limitation of autoreactive T cells response and proliferation and decreases in IL-1β, IL-6, IL-17, MMP-3, and, most importantly TNF-α [ 116 ].…”
Section: Ra Markers and Most Common Cytokines—potential Therapeutic Targetsmentioning
confidence: 99%
“…The amount of this cell subset has been expanded in ageing and pathogenic situations, such as chronic viral infections and autoimmune diseases, being widely described in RA patients [ 4 ]. In RA disease, it has been shown that CD4+CD28 null T lymphocytes and IL-15 levels are significantly increased in the blood and synovial fluid of these patients, suggesting an active role of both of them in the maintenance of inflammation in the target tissue, which could be correlated with the immunopathology and clinical activity of the disease [ 9 , 10 , 11 , 12 ]. Based on all this, we decided to study the migratory capacity of these CD4+CD28 null T lymphocytes and the effect that IL-15 could have in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, elevated serum and synovial fluid levels of IL-15 have been detected in RA patients, suggesting an important role of this cytokine in disease immunopathology and a correlation with clinical activity [ 10 , 11 ]. As a result, IL-15 has been recently proposed as a biomarker candidate for prediction of the development of RA, especially in the early phase of disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%